The economics of capital allocation in firms: Evidence from internal capital markets - Daniel Hoang; Sebastian Gatzer; Martin E. Ruckes (Karlsruher Institut für Technologie (KIT), Institut für Volkswirtschaftslehre (ECON), 2018)
We analyze a unique survey dataset to examine the (micro)foundations of capital allocation in firms. Firms employ systems of interconnected measures to counteract agency problems, including layers of approval, divisional budgets, reporting requirements, and compensation schemes. When making funding decisions, top management relies heavily on top-level, nonfinancial information. However, substantial parts of the capital budget do not require top management approval as firms trade off the benefits and costs of decentralization. Even firms with active internal capital markets tilt capital allocation toward relatively even distributions. Within-firm agency problems may result in divisions' restricted access to internal capital.
urn:nbn:de:swb:90-798861
Keywords: G31; G32; 330